Burden of thyroid cancer in the older adult aged 60 and over from 1990 to 2021 and forecast of the situation in 2030 - Fang, Hanxu; Bian, Yongshuai; Yang, Haoran; Shen, Xi; Li, Yaqi; Yue, Shuling; Xiao, Shuyu; Lu, Yuzhen; Qian, Qingzeng; Shen, Fuhai (Frontiers in Oncology, 2025)
BackgroundThis article aims to analyze the trends in global thyroid cancer mortality rate (ASMR) and disability adjusted life years (DALYs) from 1990 to 2021, and predict changes in disease burden by 2030. Through global data comparison and analysis, this study explores the impact of gender, age, and socioeconomic development level (SDI) on thyroid cancer mortality and disease burden.MethodThis study is based on data from the Global Health Data Exchange (GHDx) and analyzes the trends of thyroid cancer deaths, age-standardized mortality rate (ASMR), and DALYs over the period from 1990 to 2021. The annual average rate of change (EAPC) of the data was analyzed using a joinpoint regression model. Additionally, stratified analyses were conducted by gender, age group, and SDI, and the burden of thyroid cancer for the year 2030 was projected.ResultGlobal thyroid cancer deaths increased from 2,198 in 1990 to 5,255 in 2021. Despite the rise in total deaths, ASMR remained stable at 0.07/100,000 for females and 0.05/100,000 for males. DALYs increased from 61,815 to 144,955, with an average annual growth rate of 0.38%. The burden on men rose significantly, while the increase was slower for women. Regions with higher SDI showed a slight decrease in burden, whereas low-SDI regions saw an increase, with an annual growth rate of 0.76%. Fiji had the highest burden, with an ASMR of 0.25 and AS-DALYs of 6.07. Female mortality and disease burden were higher than in males, particularly among those aged 85 and above.ConclusionThe global disease burden of thyroid cancer has been increasing, particularly in the older adult. While high-SDI regions experienced a decrease in burden, low-SDI regions saw an increase. Predictions suggest that by 2030, the mortality rate and disease burden may remain stable with slow annual changes. However, attention should be given to the growing burden in low-income areas and the impact of socio-economic factors.